Randomized feasibility study of suction‐tube uterine tamponade for postpartum hemorrhage. Issue 3 (8th July 2019) - Hofmeyr, G. Justus; Middleton, Katrin; Singata‐Madliki, Mandisa
Abstract: Objective: To identify an inexpensive catheter suitable for uterine suction tamponade (UST) for postpartum hemorrhage and assess its functionality. Methods: Randomized, single‐center, double‐blind feasibility study in East London, South Africa, among 45 women undergoing cesarean delivery between October and November 2018. A search of medical supply websites for catheters with predefined characteristics (inexpensive, flexible, wide‐bore, circumferentially‐arranged side apertures, rounded tip) identified the FG36 Levin stomach tube. During cesarean, the tube was placed in the uterus and connected transvaginally to a suction unit. Participants were randomized via a computer‐generated random sequence to early (after uterine closure; n=24) or delayed (after skin closure; n=21) UST. Results: The tube functioned well with respect to stability in the uterus and aspirating blood from the uterine cavity without blockage. Blood loss was similar between the groups (mean difference, 7.3 mL; 95% confidence interval, −61 to 75; P =0.433), as were secondary outcomes. There were no complications. Absolute effectiveness was not tested because there was no non‐suction group. Conclusion: The FG36 Levin tube was found to be a suitable device for "suction‐tube uterine tamponade". There was no difference in functionality between early and late UST. Future trials should assess the effectiveness of this approach for postpartum hemorrhage. Clinical trial registration: Registered in the Pan African Clinical Trial Registry as PACTR201809584199573. Abstract : An inexpensive FG36 Levin stomach tube was found to be a suitable device for testing the effectiveness of uterine suction tamponade for postpartum hemorrhage.